Comparative Study of Sharia Economic Practices and Socialist Economics - Sofyan Abas (JURNAL SAINS SOSIAL DAN HUMANIORA (JSSH), 2026)
A country's economic system constitutes the framework, rules, and mechanisms used to manage production, distribution, consumption, and services to achieve prosperity. The fundamental differences between economic systems lie in how factors of production, resources, and ownership are regulated. In some systems, individuals possess all factors of production, while in others, resources are held collectively by the state. Islamic economics, as an alternative system, emphasizes principles based on the Qur'an and Sunnah, advocating justice, equitable distribution, and a profit-sharing system, contrasting with socialist economics which is grounded in collectivism and state control. This paper compares both systems in terms of philosophy, mechanisms, and their impacts on growth and social justice, demonstrating that Islamic economics has consistent characteristics and adaptability over time, capable of balancing economic growth with social equity.